Radiation dose escalation or longer androgen suppression for locally advanced prostate cancer? Data from the TROG 03.04 RADAR trial. Issue 3 (June 2015) - Denham, James W.; Steigler, Allison; Joseph, David; Lamb, David S.; Spry, Nigel A.; Duchesne, Gillian; Atkinson, Chris; Matthews, John; Turner, Sandra; Kenny, Lizbeth; Tai, Keen-Hun; Gogna, Nirdosh Kumar; et al.
Abstract Background The relative effects of radiation dose escalation (RDE) and androgen suppression (AS) duration on local prostatic progression (LP) remain unclear. Methods We addressed this in the TROG 03.04 RADAR trial by incorporating a RDE programme by stratification at randomisation. Men were allocated 6 or 18 months AS ± 18 months zoledronate (Z). The main endpoint was a composite of clinically diagnosed LP or PSA progression with a PSA doubling time ⩾6 months. Fine and Gray competing risk modelling with adjustment for site clustering produced cumulative incidence estimates at 6.5 years for each RDE group. Results Composite LP declined coherently in the 66, 70 and 74 Gy external beam dosing groups and was lowest in the high dose rate brachytherapy boost (HDRB) group. At 6.5 years, adjusted cumulative incidences were 22%, 15%, 13% and 7% respectively. Compared to 6 months AS, 18 months AS also significantly reduced LP (p < 0.001). Post-radiation urethral strictures were documented in 45 subjects and increased incrementally in the dosing groups. Crude incidences were 0.8%, 0.9%, 3.8% and 12.7% respectively. Conclusion RDE and increasing AS independently reduce LP and increase urethral strictures. The risks and benefits to the individual must be balanced when selecting radiation dose and AS duration.